Cementum structure in Beluga whale teeth. (15th January 2017) - Stock, S.R.; Finney, L.A.; Telser, A.; Maxey, E.; Vogt, S.; Okasinski, J.S.
Graphical abstract: Abstract: A large fraction of the volume of Beluga whale ( Delphinapterus leucas ) teeth consists of cementum, a mineralized tissue which grows throughout the life of the animal and to which the periodontal ligaments attach. Annular growth bands or growth layer groups (GLGs) form within Beluga cementum, and this study investigates GLG structure using X-ray fluorescence mapping and X-ray diffraction mapping with microbeams of synchrotron radiation. The Ca and Zn fluorescent intensities and carbonated hydroxyapatite (cAp) diffracted intensities rise and fall together and match the light-dark bands visible in transmitted light micrographs. Within the bands of maximum Ca and Zn intensity, the ratio of Zn to Ca is slightly higher than in the minima bands. Further, the GLG cAp, Ca and Zn modulation is preserved throughout the cementum for durations >25 year. Statement of significance: Cementum is an important tooth tissue to which the periodontal ligaments attach and consists primarily of carbonated apatite mineral and collagen. In optical microscopy of cementum thin sections, light/dark bands are formed annually, and age at death is determined by counting these bands. We employ synchrotron X-ray diffraction and X-ray fluorescence mapping to show the bands in Beluga whale cementum result from differences in mineral content and not from differences in collagen orientation as was concluded by others. Variation in Zn fluorescent intensity was found to be very sensitive indicator of changing biomineralization and suggest that Zn plays an important role this process.